Study on Frosting of Air- Cooled Heat Pump Evaporator - Zhang Zhe; Tian Jinjin (Zhileng xuebao)
A mathematical model of air-cooled heat pump finned-tube evaporator was been set up to calculate local performance of the evaporator.The model considers the difference of heat and mass transfer under dry,wet,and frosting conditions and the frost formation varying along tubes.The ordinary finned-tube evaporator was studied theoretically.The computing result shows that the frost layer is not very uniform on the evaporator and it reduces heat transfer of the evaporator.An improved evaporator structure was developed and the heat transfer falling rate of the ordinary evaporator is1.5times larger than that of the improved one.The numerical results are in good agreement with the experimental data.